Analisis Kompetensi Sosial Guru Sekolah Dasar Gugus IV Kecamatan Sukajadi Kota Pekanbaru - Yasiko, Dinni; Guslinda, Guslinda; Syahrilfuddin, Syahrilfuddin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2021)
This study aims to analyze the social competence of elementary school teachers in cluster IV,Sukajadi District, Pekanbaru City. The type of research used in this research is descriptiveresearch with a quantitative approach (descriptive-quantitative). The population in this studyconsisted of teachers totaling 47 people. The sample in this study was 47 people. The results of thestudy on indicators of being inclusive, acting objectively, and not discriminating because ofconsiderations of gender, religion, race, physical condition, family background andsocioeconomic status were 85.02% with the category